Vergleich von Belastungs- EKG und Radionuklid- Ventrikulographie bezüglich des Nachweises einer Myokardischämie bei isolierten Stenosen des Ramus interventricularis anterior - Klepzig, H., jr.; Standke, R.; Baum, R. P.; Tezak, S.; Mildenberger, D.; Maul, F. D.; Hör, G.; Kaltenbach, M. (Nuklearmedizin - NuclearMedicine, 1988)
21 patients with LAD-stenoses of at least 70% and 21 patients with LAD- stenoses and additional intramural anterior wall infarctions were studied. 20 patients without heart disease or after successful transluminal coronary angioplasty and 18 patients with intramural anterior wall infarction after successful transluminal dilatation of the LAD (remaining stenosis maximal 30%) served as controls. The normal range of global and regional left ventricular ejection fraction response to exercise was defined based on the data of 25 further patients without relevant coronary heart disease. Thus, a decrease in global ejection fraction and regional wall motion abnormalities were judged pathological. All patients were comparable with respect to age, ejection fraction at rest and work load. Myocardial ischemia could be detected by the exercise ECG in 81 % of all patients without infarction and in 71 % of patients with infarction. The corresponding values for global left ventricular ejection fraction were 76% and 81 %, respectively, and for regional ejection fraction 95% in both groups. No false-positive exercise ECGs were observed in the healthy controls and 2 (11 %) in the corresponding group with intramural infarction. The global ejection fraction was pathological in 1 (5%) healthy subject without infarction and in 3 (17%) corresponding patients with infarction. Sectorial analysis revealed 5 and 22%, respectively. Our findings suggest that the exercise ECG has a limited sensitivity to detect myocardial ischemia in patients with isolated LAD-stenoses and intramural myocardial infarction. Radionuclide ventriculography yields pathological values more often; however, false-positive results also occur more frequently.